Recycling in the GARDEN : REUSING EVERYDAY ITEMS - Youngman, Angela ([United States] : Pen and Sword, 2022)
People are becoming more aware of the environment and their impact on it. Over the past decades we have become an increasingly consumerist based society. From a world in which recycling was common, single use became the norm. This throwaway society is unsustainable. Sustainable gardening results in the creation of an environmentally friendly area in which natural predators thrive and soils are naturally replenished. Discover innovative and simple ways of recycling everything from water to materials in the garden. Practical examples show recycling in action turning unwanted items into useful features such as bottle edging, footpaths made from tyres, garden forks into table lamps, broken pottery to mosaics and tree roots into lush garden stumperies. Recycling, reusing and upcycling in the garden can make a difference helping you save money by using less water, making your own compost, choosing energy efficient equipment and by giving everyday items a totally new function. Instead of a throwaway society, we are increasingly looking at ways of reducing our use of increasingly scarce resources, turning plastic into paths, using solar energy and conserving water. Natural recycling of plant material and sustainable gardening is increasingly popular. This book helps search for creative ideas that can conserve resources, and save you money. Water is no longer cheap, so the book suggests many ways that you can re-use water and get free rainwater. The book helps you with places you may not think of looking for free and cheap material, such as reclamation yards, factories, restaurants and hospitals. Let your imagination run free without needing much skill and without breaking the bank.
Includes index.
Keywords: Recycling (Waste, etc.); Gardening